OXYGEN MONITORING IN NEWLY BORN IN INPATIENT NEONATAL INTENSIVE CARE UNIT (Fiep Bulletin - online, 2014)
Objective: Oxygen therapy in newborns is a systematic and rational therapeutic oxygen, administered at concentrations or pressures higher than the ambient atmosphere, more than 21 %, to correct or mitigate deficiencies O2 or hypoxia. In practice the amount of oxygen given to an RN should be the minimum necessary to maintain 50-80 mmHg PaO2 and/or hemoglobin saturation between 90 and 95%. Methods: This is a study of cause and effect of quantitative and qualitative, so direct, and field epidemiology, which evaluated mode, device supply, FiO2 and saturation of all patients who received newborn indication of oxygen in Neonatal Intensive Care Unit ( ICU - N ) of the Local Hospital in the period from February to September 2013. Results: The results obtained through the collection of data show that 100 % of patients were in the network, the devices used were 23.3 % with TOT, 10 % used catheter O2 and 56.6 % were doing stand with halo. Still, comparing the devices with the amount of FiO2 supplied and saturation infants with nasal catheter were average with a FiO2 of 0.43 ± 0.15 and saturation of 96 ± 3.4 %. Individuals who were with Halo had a FiO2 of 0.36 ± 0.11 and saturation of 96 ± 2.1 % and those who were with TOT, mean FiO2 and saturation were 0.37 ± 0.21 and 97 ± 2.5 % respectively. In total the average FiO2 supplied and saturation were 0.38 ± 0.11 and 96.13 ± 2.19 % respectively. Conclusion: The oxygen was administered via a network of oxygen, the devices used were mostly the mechanical ventilator, the halo and nasal catheter. Among the values ??found, highlighted the presence of inspired oxygen concentrations above recommended, and PaO2 .
Keywords: oxygen; oxygen therapy; neonates; intensive care unit